O trabalho interprofissional e as competências colaborativas na estratégia de Saúde da Família. - Machado, Karla da Silva (2023)
Collaborative interprofessional practice in health is an innovative strategy for overcoming the global crisis in health services. Through this practice it is possible for the health workforce to be better prepared to deal with the health demands of the population. Professional practice based on competencies has been pointed out by various studies as being able to contribute to increasing the quality of health care. This study aimed to analyze the development of interprofessional collaborative practices in the light of competencies, in the Family Health and NASF-AB teams in the municipality of Sobral, CE. It was decided to carry out a qualitative, exploratory and descriptive study. Two groups of professionals from family health teams in the municipality of Sobral-CE took part in the research. Data was collected using the Focus Group technique and the construction of the Action Map. The data was analyzed using the thematic analysis technique and in the light of the theoretical framework of the principles, domains and competences of the Canadian Interprofessional Health Collaborative (CIHC). The actions identified as the main activities carried out in a shared manner with other professional categories were: home visits and team meetings. The results showed that the following collaborative competencies were present in the work process analyzed: interprofessional communication, teamwork and patient-, family- and community-centered care. Among the challenges identified for advancing the development of collaborative competencies, the professionals pointed to the changes resulting from Previne Brasil, which reduced incentives for interprofessional actions, team meetings, reduced financial resources, as well as prioritizing clinical-assistance actions to the detriment of actions aimed at comprehensive care. The study found the development of actions based on the collaborative competencies postulated by the CIHC, which are close to the concept of interprofessional work and the implementation of its practice in the scenario investigated.